TO SPEAK OR NOT TO SPEAK? THE WILLINGNESS TO SPEAK ENGLISH AMONG ENGLISH DEPARTMENT STUDENTS - Azzahra, Shofwa; Aisyiyah, Muhsiyana Nurul; Rohadi, Tedi; Sandy, Fadillah (IAIN Syekh Nurjati Cirebon, 2024)
Adapting to the habits of communicating in English poses a significant challenge for freshmen of English Education Department in Indonesian context. They are required to listen to their lecturers’ explanation in English as well as to use English during classroom discussion. This research aims to explore the factors influencing the willingness to speak English. This study used mixed methods with the explanatory design. The quantitative data were collected by means of survey. As many as 40 first-year students majoring in English education in an Islamic state university in Cirebon filled in the questionnaire. The qualitative data were collected by interviewing 8 students. The quantitative data were analyzed with descriptive statistics while the qualitative data was used to corroborate the analysis of the quantitative findings. The results showed that the factors influencing students' willingness to speak are task type, topic of discussion (topics of familiarity, topics of interest, and topic preparation), interlocutor, students' personal characteristics (fear of negative evaluation, fear of correctness of speech, personality (shyness), self-confidence, teacher's role, and seating location.